Maintenance and differentiation of human ES cells on polyvinylidene fluoride scaffolds immobilized with a vitronectin‐derived peptide. Issue 5 (8th October 2020) - Park, Sang Eun; Yeon, Gyu‐Bum; Goo, Hui‐Gwan; Seo, Dong Sik; Dayem, Ahmed A.; Lee, Kyung Eun; Park, Hyun‐Mee; Cho, Ssang‐Goo; Kim, Dae‐Sung
Abstract: Polyvinylidene fluoride (PVDF) is biocompatible, easy to fabricate, and has piezoelectric properties; it has been used for many biomedical applications including stem cell engineering. However, long‐term cultivation of human embryonic stem cells (hESCs) and their differentiation toward cardiac lineages on PVDF have not been investigated. Herein, PVDF nanoscaled membrane scaffolds were fabricated by electrospinning; a vitronectin‐derived peptide‐mussel adhesive protein fusion (VNm) was immobilized on the scaffolds. hESCs cultured on the VNm‐coated PVDF scaffold (VNm–PVDF scaffold) were stably expanded for more than 10 passages while maintaining the expression of pluripotency markers and genomic integrity. Under cardiac differentiation conditions, hESCs on the VNm–PVDF scaffold generated more spontaneously beating colonies and showed the upregulation of cardiac‐related genes, compared with those cultured on Matrigel and VNm alone. Thus, VNm–PVDF scaffolds may be suitable for the long‐term culture of hESCs and their differentiation into cardiac cells, thus expanding their application in regenerative medicine. Abstract : Vitronectin‐derived peptide‐mussel adhesive protein fusion (VNm)–polyvinylidene fluoride scaffolds improved the cardiac differentiation of human embryonic stem cells.